Calculation of multi-group migration areas in deterministic transport simulations. (1st June 2020) - Liu, Zhaoyuan; Smith, Kord; Forget, Benoit
Highlights: The relationship of migration area with mean squared displacement is demonstrated. The analytic MG migration areas are derived and validated vs. Monte Carlo. Condensation of transport XS is inverse flux weighted to preserve migration area. Abstract: Recent work on the Cumulative Migration Method (CMM) has demonstrated that it is possible to define multi-group transport cross sections directly from Monte Carlo spectral calculations by utilizing edits of the energy-dependent neutron migration areas. However, it is difficult to demonstrate that downstream deterministic transport calculations actually preserve Monte Carlo migration areas. This paper addresses this issue by: 1) demonstrating the relationship of migration area with the concept of mean squared displacement, 2) deriving, and validating vs. Monte Carlo, an analytic expression for computing one-group migration areas for a homogeneous medium with energy-independent cross sections, 3) deriving, and validating vs. Monte Carlo, an analytic expression for computing multi-group migration areas for a homogenized medium with energy-dependent cross sections, and 4) rigorously proving that energy condensation of multi-group transport cross section must be inverse flux weighted in order to preserve Monte Carlo neutron migration areas.